Taurochenodeoxycholic Acid Increases cAMP Content via Specially Interacting with Bile Acid Receptor TGR5 - Youchao Qi; Linkai Shi; Guozhen Duan; Yonggui Ma; Peifeng Li (Molecules, 2021)
Taurochenodeoxycholic acid (TCDCA) is one of the main components of bile acids (BAs). TCDCA has been reported as a signaling molecule, exerting anti-inflammatory and immunomodulatory functions. However, it is not well known whether those effects are mediated by TGR5. This study aimed to elucidate the interaction between TCDCA and TGR5. To achieve this aim, first, the TGR5 eukaryotic vector was constructed. The expression level of TGR5 in 293T cells was determined by immunofluorescence, real-time quantitative PCR (RT-PCR, qPCR), and Western blot. The luciferase assay, fluorescence microscopy, and enzyme-linked immunosorbent assay (ELISA) were recruited to check the interaction of TCDCA with TGR5. TCDCA treatment in 293T cells resulted in TGR5 internalization coupled with a significant increase in cAMP luciferase expression. Our results demonstrated that TCDCA was able to bind to the TGR5 receptor and activate it. These results provide an excellent potential therapeutic target for TCDCA research. Moreover, these findings also provide theoretical evidence for further TCDCA research.